2022
DOI: 10.1002/acr.24718
|View full text |Cite
|
Sign up to set email alerts
|

In the Dark About Physical Activity – Exploring Patient Perceptions of Physical Activity After Elective Total Knee Joint Replacement: A Qualitative Study

Abstract: Objective. The study aimed to explore patient perceptions of and motivations for physical activity after total knee joint replacement.Methods. Participants were purposively sampled after completing a public outpatient rehabilitation exercise group. Semistructured interviews were completed with 22 participants (mean age 70 years, 45% women) 6 to 12 months after total knee joint replacement. Interviews were audiotaped and transcribed verbatim. Themes were identified by an inductive and iterative process of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…This suggests a role for increasing physical activity in patients with significant comorbidities prior to undergoing THR to maximise post-operative outcomes. However, there is inadequate knowledge and motivation for adhering to physical activity recommendations among people with OA and concomitant comorbidities who undergo joint replacement surgery, which poses a barrier to change [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a role for increasing physical activity in patients with significant comorbidities prior to undergoing THR to maximise post-operative outcomes. However, there is inadequate knowledge and motivation for adhering to physical activity recommendations among people with OA and concomitant comorbidities who undergo joint replacement surgery, which poses a barrier to change [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential participants were eligible if they were 18 years or older, conversant in English and were 6–26 weeks after primary elective total knee joint replacement secondary to osteoarthritis. People with primary elective knee joint replacement were selected as this was the group where a knowledge gap about physical activity recommendations had been identified (Hawke et al., 2022). People with a documented medical history of cognitive decline were not eligible because of potential difficulties understanding the infographic.…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge of a health behaviour (in this instance, physical activity) is a primary component of behaviour change theories and is a prerequisite for behaviour change interventions to successfully increase physical activity after joint replacement (Bandura, 2004). However, a recent qualitative study found that people with knee joint replacement lacked basic knowledge of physical activity constructs including physical activity recommendations (Hawke et al., 2022). Therefore, the knowledge gap specific to physical activity observed in people after knee replacement needs to be addressed so that the effectiveness of subsequent behavioural change strategies is optimised (Hawke et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations